MOTHER'S LOVE AS AN INSPIRATION FOR CREATING PAINTING WORKS - Guhmana, Teguh Djaka Sudarmana (ARTISTIC : International Journal of Creation and Innovation, 2024)
The study of the creation of this work began with an interest in mothers’ love in sincerely nurturing their children and families. Once elaborated, a mother's love is eventually the fruits of the spirit (Galatians 5:22-23). This creation study uses an emic approach to understand the meaning of maternal love as perceived by mothers at the Bhakti Kasih Bunda nursing home in Surakarta. This creation study stage was divided into several steps in creating the work: (1) data collection through field observations, literature studies, and in-depth interviews with mothers at the Bhakti Kasih Bunda nursing home as well as Christian and Confucian religious leaders; (2) data analysis and conclusions as a source of work creation; (3) the process of creating works, which involves stages of experimentation, contemplation, and execution. he result of this creation study was a painting that uses mixed media with collage techniques. The works were divided into four parts based on subject matter, all of which are metaphors for maternal love as the fruit of the spirit. The four parts are the earth and the solar system, humans, animals, and plants.